BHIKHU PAREKH CRITICS TOWARD MODERN PLURALISM - Iwanebel, Fejrian Yazdajird (Teosofia: Indonesian Journal of Islamic Mysticism, 2016)
Pluralism is judged by some thinkers as a response to their dissatisfaction with monism. The factual realities have made a self-evident that society's culture is plural. In this paper the author tries to describe three prominent figures who discuss about pluralism and the weaknesses of their thoughts. The author stands on the work of Bhikhu Parekh entitled "Rethinking Multiculturalism; Cultural Diversity and Political Theory". In Parekh's view, the three thinkers have criticized monism and wanted to propose the idea of cultural pluralism. Unfortunately, they are stuck on moral values which are integral and universal. So they are just returning to moral monism in explaining the reality of a diverse society. In this dialect, multiculturalism becomes a new alternative for intercultural dialogue that carries the mission of equality and freedom of expression which is accompanied by positive reciprocity leading to a dynamic civilization of constructive human life.